TINJAUAN YURIDIS BENTUK USAHA TETAP PENYEDIA LAYANAN APLIKASI DAN KONTEN BERBASIS INTERNET DI INDONESIA - Ragil Prastyawan; Budi Santoso; Tunggul Ansari (Universitas Airlangga, 2017)
Permanent establishment is an expansion of foreign corporations which cannot perform any legal act in Indonesia. For that reason, it cannot be created into a corporation. Foreign corporations providing online application or internet-based content perform virtually their activities of their operation in Indonesia. The legalisation of permanent establishment created by foreign corporations is ruled in ministerial circular letter of the Ministry of Information and Communication no. 3 of 2016. One of the matters ruled in Presidential Decree no. 44 of 2016 is business field of information and communication. It is categorised into business field with certain requirements. Eventually, the regulation allows them to invest and form a corporation in Indonesia. Additionally, this regulation is created in order to keep everything in order and benefit from foreign corporations' investments in Indonesia. The method used in this study is normative method with three approaches: statute approach, case study approach, and conceptual approach. The result of this study shows that business field providing online application or internet-based content mentioned in ministerial circular letter of the Ministry of Information and Communication no. 3 of 2016 can be categorised into information and communication technology sector as also mentioned in Presidential Decree no. 44 of 2016 which regulates lists of open business field and closed business field with certain requirements. According to the regulation, permanent establishment formed by foreign corporations in Indonesia must be in the form of limited liability company.